Delimiting the concept of organizational commitment: empirical evidence of the overlap between the entrenchment and the continuance mindset - Rodrigues, Ana Carolina de Aguiar; Bastos, Antônio Virgílio Bittencourt; Moscon, Daniela Campos Bahia (Organizações & Sociedade, 2019)
In the research agenda on organizational commitment, the three-dimensional model of Meyer and Allen is still extensively used, despite the fact that it has been the focus of discussions about conceptual and empirical problems, especially those related to one of its dimensions (continuance commitment). This study introduces to the existing debate the concept of organizational entrenchment, as the worker's tendency to remain due to his evaluation of his employability, his employment alternatives outside the organization, and the costs associated with leaving the company. In the career field, researchers found evidence of overlap between entrenchment and continuance commitment. In this study, we aimed to test the hypothesis of overlap between these constructs within the organizational target, using structural equation modeling. The sample consisted of 721 workers from different organizations and states in Brazil. We used SPSS 13.0 and AMOS 16.0 software. The two covariance models, both with good fit indices, provided evidence of overlap. In spite of the fact that the hypothesis was confirmed, we recommend further studies aimed at gathering additional empirical indicators showing that the continuance component represents the same phenomenon as organizational entrenchment, justifying its detachment from the concept of commitment.